Polymorphism of the second type angiotensin II receptor's gene in women with essential hypertension and the corresponding features of structural and functional parameters of myocardium - O. O. Sakovych; V. M. Zhebel; T. V. Polishchuk; S. V. Franchuk; L. M. Sursaieva (Zaporozhye State Medical University, 2018)
Abstract Objective. To improve the diagnosis of predisposition to Essential arterial hypertension (EH) and Chronic heart failure (CHF) in postmenopausal age's women by determining the polymorphic genotypes of the first type angiotensin II receptor's gene (AT1-R) and the corresponding structural and functional state of myocardium. Materials and methods. The study involved 180 women of postmenopausal age, they were residents of Podillya Region of Ukraine. 80 women without signs of cardiovascular diseases were the control group, 100 women with EH included the main study's group. Genotyping of AT1-R was carried out using the polymerase chain reaction. The distribution of the frequencies of genotypes AT1-R was checked in accordance with the Hardy-Weinberg equilibrium law. The structural and functional parameters of myocardium were evaluated using an echocardiography. The left ventricular's systolic function was preserved in cases where the left ventricular's ejection fraction was more than 40 %. Mathematical processing was performed using the standard statistic package Statistica 6.0. Results. In patients with EH genotype AC was detected most often (49 %), AA and AC genotypes weer determined in 40 % and 11 % of patients (РАА-СС≤ 0.05, РАС-СС≤ 0.05) respectively. Carrying allele C of the AT1-P gene was associated with a higher probability of future occurrence of CHF in patients with EH, more significant structural disorders of myocardium and disturbances of systolic and diastolic functions of left ventricle (LV) such as pseudonormal and restrictive types. Conclusions. Allele C associates with the presence of EH and a greater probability of occurrence of CHF in postmenopausal women, residents of Podillya Region, more pronounced disturbances in the structure of myocardium, with diastolic and systolic dysfunctions of LV. Developed mathematical models help to determine approximately the structure of AT1-R according to the parameters of cardiac hemodynamics in the case of impossibility of laboratory investigation.